Coronary microvascular disease is associated with arterial stiffness in patients with ischemia and no obstructive coronary arteries. (3rd May 2023) - Sakalidis, A; Dimitriadis, K; Dri, I; Leontsinis, I; Mantzouranis, E; Ntalakouras, I; Doundoulakis, I; Iliakis, P; Vlachakis, P; Beneki, I; Siafi, I; Tsioufis, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Existing data suggest that stable angina pectoris with no obstructive coronary artery disease is associated with increased risks of major adverse cardiovascular events. There is a gap in the current literature regarding the possible association between higher aortic stiffness and myocardial ischemia in this special population. Arterial Stiffness (AS) is an independent risk factor for cardiovascular disease, directly related to increased coronary atherosclerosis, an entity frequently encountered in hypertensive patients. Purpose: The aim of this study is to determine whether arterial stiffness is increased in patients with Coronary Microvascular Dysfunction (CMD) compared to hypertensives controls. Methods: We examined 21 hypertensive patients [9 female, 39%, mean age: 61.2±9.9 years, mean office blood pressure (BP) : 139/86±18/10 mmHg] and 25 CMD patients (16 female, 64%, mean age : 57.9±4.8 years, average office BP: 127/77±18/10 mmHg). In the group of patients with chronic angina pectoris, CMD was defined by a standardized systematic protocol in which coronary flow reserve (CFR) and index of microvascular resistance (IMR) were measured in the left anterior descending coronary artery using a temperature/pressure sensor-tipped guidewire. CMD patients were classified into 2 groups, structural and functional endotype, based on commonly used cut-offs (impaired CFR < 2.5, increased IMR ≥ 25). Functional CMD was defined as abnormal CFR in combination with normal IMR and structural CMD as abnormal CFR with abnormal IMR. In addition, in all participants, arterial stiffness was assessed using aortic augmentation index (AIx), derived from the analysis of central pulse waveforms, recorded by applanation tonometry directly from the radial artery. Results: In CMD group, mean CFR and IMR were 1.6 ± 0.9 and 43.9± 30 IU, respectively. Of the 25 patients with abnormal CFR, 8 (32%) had normal IMR consistent with functional CMD endotype, and 17 (68%) had abnormal IMR consistent with structural endotype. AIx was found increased in CMD patients compared to asymptomatic hypertensives (36.44±11.1 vs 25.4±11.6%, p=0.024). This difference in AIx between the CMD and asymptomatic hypertensive controls was found to be statistically significant after adjustment for gender and age (p<0.05). No statistically significant difference was found in body mass index, renal function, history of dyslipidemia, diabetes mellitus and smoking between the two groups (p=NS). Conclusion: Arterial stiffness was found increased in patients with CMD compared to hypertensives. These results suggest that therapies targeting vascular stiffening could provide additional clinical benefit in this special category of patients with impaired coronary microvasculature.